Fiscal Adjustment in the Gulf Countries : Less Costly than Previously Thought - Fouejieu, Armand (IMF Working Papers; Working Paper ;, 2018)
This paper estimates fiscal multipliers for the Gulf Cooperation Council (GCC) countries. Using OLS panel fixed effects on a sample of six countries from 1990-2016, results indicate that GCC fiscal multipliers have declined in recent years which would make the on-going fiscal consolidation less costly than previously thought. Though both capital and current multipliers have declined in recent years, capital multipliers are larger than current multipliers, which implies that reducing (less productive) current spending will help limit the adverse impact of such measures on growth.